Effect of Aerobic Exercise of Three Different Intensities on Intraocular Pressure. - Bulson, Ryan (Optometry & Visual Performance, 2020)
Background: Previous studies have demonstrated that aerobic exercise is accompanied by an acute reduction in intraocular pressure; however, much of this work suffers from methodological flaws and/or poor description of experimental parameters. The purpose of this study was to determine the acute effects of aerobic exercise of varying intensity on intraocular pressure. Methods: Twenty-five volunteer participants with normal intraocular pressure (17.17 ± 3.85 mmHg) completed the study. Each participant completed a standardized step test to estimate maximal oxygen uptake, which was used to prescribe individualized treadmill speeds representing three exercise intensities (95%, 65%, and 45% maximal oxygen uptake). In a random and repeated design, participants completed 2.0 km at each intensity. This experimental design isolated power (exercise intensity) as the variable of interest, while holding total work constant for each condition (2.0 km). Baseline intraocular pressure, heart rate, and blood pressure were measured prior to each exercise intensity and again at time 0, 5, 10, and 20 minutes post-exercise. Results: Aerobic exercise using individualized treadmill speeds equivalent to 95%, 65%, and 45% of estimated maximal oxygen uptake significantly reduced intraocular pressure for all intensitiesrelative to baseline (p<0.01). The 95% intensity showed a more significant intraocular pressure reduction than either the 65% and 45% intensities (p<0.001). Conclusion: All exercise intensity levels were associated with an acute reduction of intraocular pressure with higher intensities demonstrating a larger reduction in intraocular pressure. Further study is needed to determine the duration of intraocular pressure reduction following exercise at different intensity levels.